2017
DOI: 10.1017/s1368980017002476
|View full text |Cite
|
Sign up to set email alerts
|

Employment status and temporal patterns of energy intake: Nutrition and Health Survey in Taiwan, 2005–2008

Abstract: Adults' temporal patterns of energy intake, which varied with their employment status, affected their dietary quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…In a small study based on 16-d dietary record, the Japanese eating pattern was, on average, characterised by small snacks (11 % of total energy intake), as well as relatively large three main meals (percentage of total energy intake: 21 % for breakfast, 32 % for lunch and 40 % for dinner) (32) . A similar eating pattern (three main meals, with infrequent snacks particularly at night) was also observed in a representative sample of Taiwanese adults (33) . It would be of interest to clarify if this eating pattern is prevalent in East Asian countries with similar social and cultural backgrounds.…”
Section: Discussionsupporting
confidence: 73%
“…In a small study based on 16-d dietary record, the Japanese eating pattern was, on average, characterised by small snacks (11 % of total energy intake), as well as relatively large three main meals (percentage of total energy intake: 21 % for breakfast, 32 % for lunch and 40 % for dinner) (32) . A similar eating pattern (three main meals, with infrequent snacks particularly at night) was also observed in a representative sample of Taiwanese adults (33) . It would be of interest to clarify if this eating pattern is prevalent in East Asian countries with similar social and cultural backgrounds.…”
Section: Discussionsupporting
confidence: 73%
“…Although the various markers of well-being level (education, income, professional status) are correlated, they measure different phenomena and do not replace each other as indicators of a hypothetical latent social dimension [64]. In addition, numerous studies have indicated a complex relationship between employment and eating habits, associated, for example, with strategies for coping with work stress [65] as well as with heterogeneous lifestyles in strata by employment and occupational classes [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Employment status and working environment can affect dietary patterns (Chau et al, 2017). However, to our knowledge, the effect of WFH on dietary patterns is largely unknown.…”
Section: Introductionmentioning
confidence: 99%